Association of HLA-DRB1 Alleles with Rheumatic Fever and Rheumatic Heart Disease: A Meta-analysis. (17th February 2022) - Poomarimuthu, Maheshkumar; Ramasamy, Thirunavukkarasu; Govindan, Ramajayam; Andiappan, Rathinavel; Nagarajan, Gunavathy; Kadiam, Sony; Mariakuttikan, Jayalakshmi
ABSTRACT: Background: Rheumatic fever (RF) and its sequel rheumatic heart disease (RHD) is an autoimmune disease caused by an abnormal host immune response to group A streptococcus (GAS) infection. The HLA class II molecules are entailed in immune-mediated infectious, inflammatory, and autoimmune diseases including RHD. However, HLA class II genes are reported to be associated with RF/RHD across different populations with a very little consistency. Objective: The aim of the study is to investigate the association between HLA class II genes and RF/RHD by meta-analysis. Methods: A comprehensive literature search was conducted to identify all relevant case-control studies published before December 31, 2019. The data were extracted using standardized form and pooled odds ratio (OR) with 95% confidence interval (CI) are calculated to assess the strength of the association between HLA class II genes and RF/RHD. Results: Thirteen studies for HLA-DRB1 alleles (1065 patients and 1691 controls) and eight studies for HLA-DQB1 alleles (644 patients and 1088 controls) were finally included. The meta-analysis showed a significantly higher frequency of HLA-DRB1*07 allele (OR = 1.68, P < .0001) in RF/RHD patients when compared to controls, while the frequency of HLA-DRB1*15 allele (OR = 0.60, P = .03) was significantly lower in RF/RHD patients than in controls. However, there were no significant differences in the frequency of HLA-DQB1 alleles between RF/RHD patients and controls. Conclusions: The results of the meta-analysis suggest that the differential presentation of autoimmune peptides by HLA-DRB1*07 (susceptible) and HLA-DRB1*15 (protective) alleles with different affinities may play a crucial role in the pathogenesis of RF/RHD.